Implementation of Tracking of a Moving Object Based on Camshift Approach with a UAV. (2016) - Coşkun, Musab; Ünal, Sencer
Abstract: In this paper, a report is presented on the findings of a study conducted on evaluating AR.Drone performance for computer vision applications. Object tracking is a challenging problem because of tracked object motion and its size changes in the scene, illumination changes and egomotion. An approach that is able to cope with those problems using an unmanned air vehicle was applied. Unmanned air vehicle has been an increasing field of research in both civilian and military applications. Among its different models, quadrotors have advantages such as high maneuverability and moving in three directions. The unmanned air vehicle used in this paper is AR.Drone. The application is implemented using version 2.4.9 of OpenCV library with C programming language in Visual Studio 2010 environment and is capable of tracking moving objects by using the front camera of AR.Drone with resolution of 640x360 and at a frame rate of 30 fps. Object tracking process is carried on independently from the distance between AR.Drone and the tracked object. Experimental results testify that object tracking is carried out successfully with AR.Drone which is a mobile platform despite of change in object's size in the scene and of illumination.